Bimbingan Teknis dan Pendalaman Materi Berbasis Coaching Clinic dalam Penyusunan RAB Sesuai PERMEN Bidang Bina Marga, Cipta Karya, dan Sumber Daya Air Se-Kabupaten Maros - Nur, Sitti Hijraini; Pongmada, Silman; Caronge, Muhammad Akbar; K, Riswal; Abdurrahman, Muh. Asad; Amiruddin, A. Arwin; Adisasmita, Sakti Adji; Umar, Hasdinar; Ishak, Rahmi Amin (Faculty of Engineering UNHAS, 2023)
The National Community Empowerment Program's village and sub-district officials who oversee development financing must execute Technical Guidance in the context of creating a Draft Cost Budget for the construction of Highways, Civil Works, and Water Resources. To help the Construction Development Institute teach and provide technical advised to all village fund managers so they can stay on task and prevent the misuse of state financial management, academics are needed. The purpose of this activity is to provide understanding to village and sub-district officials so that they prioritize planning activities, budget calculations, material needs to implementation in accordance with quality standards and good accountability. All officials throughout Maros Regency are invited to attend or send their envoys as Technical Guidance participants. Subsequently, a coaching clinic method was implemented, wherein the Construction Cost Estimate (RAB) was prepared in an intense manner to maximize training outcomes right away. This method allows us to directly examine participants' comprehension of AHSP and RAB compilation, as well as directly rectify the way participants begin calculating. From the post-test results, data on the understanding of village staff on AHSP has reached 73% and understanding in preparing the RAB has exceeded 60%. Keywords: Technical Guidance, National Community Empowerment Program's, AHSP, RAB compilation, coaching clinic.